Creativity Impact on Language Achievement: A correlational study of Iranian EFL learners - Zokaee, Mojtaba; Baghbanian, Abdolvahab; Nejad, Mohammad Abbas (Círculo de Lingüística Aplicada a la Comunicación, 2020)
This study investigated the correlation between Creativity and Language Achievement (LA) among Iranian EFL learners (n=138) from three different Iranian universities. Learners were invited through census sampling technique to participate in the study. General English questions (adapted from university entrance exam) and Self-report Creativity Test designed by Rand Sip et al. (1979) were employed for collecting data on LA and creativity, respectively. Questionnaires were distributed among the participants during the class hours by prior arrangement with teachers and learners, and were collected a few days later. SPSS statistics software was used to find the relationship between the study variables. Overall, 103 learners, aged 18 to 27, returned the questionnaires for analysis. The creativity scores ranged from 134 to 210 and the LA scores were between 0 and 16. The Pearson correlation coefficient test revealed no significant correlation between the participants’ creativity and their language achievement (r = -0.136, p =0.17).